Wound-Inducible Proteinase Inhibitors in Pepper. Differential Regulation upon Wounding, Systemin, and Methyl Jasmonate - Moura, Daniel S. (American Society of Plant Physiologists, 2001)
Seven small (approximately 6,000 D) wound-inducible proteinase inhibitor proteins were isolated from leaves of pepper (Capsicum annuum) plants that are members of the potato inhibitor II family. N-terminal sequences obtained indicated that the pepper leaf proteinase inhibitors (PLPIs) exhibit homology to two GenBank accessions that code for preproteins containing three isoinhibitors domains each that, when post-translationally processed, can account for the mixture of isoinhibitors that are reported herein from pepper leaves. A constitutive level of PLPI proteins was found in pepper leaves, and these levels increased up to 2.6-fold upon wounding of the lower leaves. Exposing intact plants to methyl jasmonate vapors induced the accumulation of PLPIs. Supplying excised young pepper plants with water through the cut stems induced PLPI proteins to levels higher than those found in intact plants, but with high variability. Supplying the excised plants with systemin did not result in an increase of PLPI levels that were statistically higher than levels found in excised plants. Gel-blot analyses of PLPI induction revealed the presence of two mRNA bands, having slightly different mobilities in agarose gels. Only the low M(r) mRNA is present in untreated control plants, and it appears to be responsible for the constitutive levels of PLPI found in leaves. Both mRNA species are wound- and methyl jasmonate-inducible. Only the low- M(r) species is weakly induced by systemin, indicating a differential expression of the two PLPI species.